2012
DOI: 10.1007/978-3-642-33314-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Coloring Algebra with Consequences for Feature-Oriented Programming

Abstract: Abstract. In 2011, simple and concise axioms for feature compositions, interactions and products have been proposed by Batory et al. They were mainly inspired by Kästner's Colored IDE (CIDE) as well as by experience in feature oriented programming over the last decades. However, so far only axioms were proposed; consequences of these axioms such as variability in models have not been studied. In this paper we discuss the proposed axioms from a theoretical point of view, which yields a much better understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…However, the analysis of that set of axioms in [13] showed that they seem to admit only very tricky and not very intuitive mathematical models, contrary to the axiom set in the present paper. We have since discovered that adding axioms A + A = 0 and A # A = A (self-interaction is idempotent) to FIA are also consistent.…”
Section: Variants Of the Axiomatizationcontrasting
confidence: 70%
“…However, the analysis of that set of axioms in [13] showed that they seem to admit only very tricky and not very intuitive mathematical models, contrary to the axiom set in the present paper. We have since discovered that adding axioms A + A = 0 and A # A = A (self-interaction is idempotent) to FIA are also consistent.…”
Section: Variants Of the Axiomatizationcontrasting
confidence: 70%